Assessing the quality of written information provision for surgical procedures: a case study in oesophagectomy. Issue 10 (12th October 2015) - Blencowe, N S; Strong, S; McNair, A G K; Howes, N; Elliot, J; Avery, K N; Blazeby, J M
Abstract : Objective: To examine the content and quality of written information provided by surgical centres for patients undergoing oesophagectomy for cancer. Design: Cross-sectional study of the content of National Health Service (NHS) patient information leaflets (PILs) about oesophageal cancer surgery, using a modified framework approach. Data sources: Written information leaflets from 41 of 43 cancer centres undertaking surgery for oesophageal cancer in England and Wales (response rate 95.3%). Eligibility criteria: All English language versions of PILs about oesophagectomy. Results: 32 different PILs were identified, of which 2 were generic tools (Macmillan 'understanding cancer of the gullet' and EIDO 'oesophagectomy'). Although most PILs focused on describing in-hospital adverse events, information varied widely and was often misleading. Just 1 leaflet described survival benefits of surgery and 2 mentioned the possibility of disease recurrence. Conclusions: Written information provided for patients by NHS cancer centres undertaking oesophagectomy is inconsistent and incomplete. It is recommended that surgeons work together with patients to agree on standards of information provision of relevance to all stakeholders' needs.